High performance graphene embedded rubber composites. Issue 99 (25th September 2015) - Song, Sung Ho; Kim, Jung Mo; Park, Kwang Hyun; Lee, Dong Ju; Kwon, O.-Seok; Kim, Jin; Yoon, Hyewon; Chen, Xianjue
Abstract : Nano-fillers have provided a big advantage for enhancing the performance of rubber composites through leading the synergy effects in the physical and chemical properties. Abstract : Nano-fillers have provided a big advantage for enhancing the performance of rubber composites through leading the synergy effects in the physical and chemical properties. However, despite various approaches having been explored, the process to make a homogenous and stable dispersion of nano-filler in the rubber matrix remains a major challenge in this field. Herein, we propose a simple and effective route for synthesizing nanocomposites of rubber with homogenous and stable dispersed low defect graphene flakes (l-GFs), which are prepared using l-GFs/SBR composites via aqueous-phase mixing of exfoliated l-GFs with SBR latex. The l-GFs embedded SBR matrix shows a remarkable improvement in the modulus and tensile strength even at the low loading rate, which is ascribed to the efficient dispersion of the l-GFs enhancing interfacial interaction with the rubber matrix. The integration of l-GFs into the SBR matrix significantly improves the thermal and electrical conductivities, as well as the gas barrier property of the rubber composites. This method is water-mediated, green and scalable, showing great potential for the production of various l-GFs-based rubber composites at an industrial level.